2012
DOI: 10.1002/art.34320
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Th17 and antigen‐specific humoral responses in CX3CR1‐deficient mice in the collagen‐induced arthritis model

Abstract: Objective CX3CR1 is a chemokine receptor that uniquely binds to its ligand fractalkine (FKN or CX3CL1) and has been shown to be important in inflammatory arthritis responses largely due to effects on cellular migration. In this study, we tested the hypothesis that genetic deficiency of CX3CR1 would be protective in the chronic inflammatory arthritis model, collagen induced arthritis (CIA). Because CX3CR1 is expressed on T cells and antigen-presenting cells, we additionally examined adaptive immune functions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 48 publications
(99 reference statements)
1
23
1
Order By: Relevance
“…Specifically, we show that in contrast to the Cx3cr1-dependent IL-23 and IL-22 induction during mucosal bacterial infection (18), Cx3cr1 ϩ/ϩ and Cx3cr1 Ϫ/Ϫ mice exhibited similar levels of expression of IL-23 and IL-22 from tongue homogenates during OPC. In addition, we found no Cx3cr1-dependent regulation of IL-17A during oral fungal infection, which is in contrast to what has been observed in the context of inflammatory colitis, collagen-induced arthritis, and experimental autoimmune encephalomyelitis (20)(21)(22).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Specifically, we show that in contrast to the Cx3cr1-dependent IL-23 and IL-22 induction during mucosal bacterial infection (18), Cx3cr1 ϩ/ϩ and Cx3cr1 Ϫ/Ϫ mice exhibited similar levels of expression of IL-23 and IL-22 from tongue homogenates during OPC. In addition, we found no Cx3cr1-dependent regulation of IL-17A during oral fungal infection, which is in contrast to what has been observed in the context of inflammatory colitis, collagen-induced arthritis, and experimental autoimmune encephalomyelitis (20)(21)(22).…”
Section: Discussioncontrasting
confidence: 99%
“…Of interest, Cx3cr1 has previously been shown to promote IL-23-dependent IL-22 production and mucosal immune responses in the context of bacterial gastrointestinal (GI) tract infection and intestinal inflammation (18,19). Similarly, it has also been found that Cx3cr1 modulates IL-17 responses, both at the mucosal level in the setting of intestinal inflammation (20) and systemically in models of experimental autoimmune encephalomyelitis and collagen-induced arthritis (21,22). Therefore, the aim of this study was to determine whether a deficiency in CX 3 CR1 impairs the production of IL-17A, IL-22, and IL-23, while enhancing susceptibility of mice or humans to mucosal Candida infections.…”
mentioning
confidence: 99%
“…Published data in other disease models show significantly reduced disease severity and T H17 infiltration in collageninduced arthritis in the absence of CX3CR1, 50 and trends toward less IL-17A in mucosal candidiasis 51 and nephrotoxic nephritis. 52 In contrast, in experimental autoimmune encephalitis, both IL-17 and IFNg production and disease severity were enhanced in CX3CR1 2/2 mice compared with WT controls, however, this effect was not T cell intrinsic.…”
Section: Cx3cr1mentioning
confidence: 89%
“…For CAIA, mice were injected on day 0 intraperitoneally with a cocktail of 5 anti-collagen monoclonals (5 mg/0.5 ml/mouse; Chondrex) and on day 3 with LPS (50 μg/0.1 ml/mouse). Mice were monitored daily for arthritis severity by a blinded observer as described (11, 12). Hind paws were isolated and fixed for 24h in Tellyesnickzky/Fekete fixative, decalcified using formic acid, and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%